2020
DOI: 10.1097/brs.0000000000003500
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Predictive Factors for Mechanical Complications After Adult Spinal Deformity Surgery

Abstract: Study Design. A retrospective multicenter observational study. Objective. To investigate correction surgeries that were performed in relatively aged patients in terms of mechanical complications (MCs) and their predictive factors. Summary of Background Data. The risk factors associated with MCs have not yet been well examined, especially in aged populations. Methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 28 publications
1
24
1
Order By: Relevance
“…Several scoring and classifications systems have been developed to guide alignment goals either based on age or PI but have not generalized well in terms of preventing PJK. 20,21,46 In "The Global Alignment and Proportion (GAP) Score," the authors concluded that alignment targets should be proportional to PI. 19 Using mechanical complications as a composite outcome, the authors categorized 4 radiographic parameters using optimal cutoffs based on the outcome of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Several scoring and classifications systems have been developed to guide alignment goals either based on age or PI but have not generalized well in terms of preventing PJK. 20,21,46 In "The Global Alignment and Proportion (GAP) Score," the authors concluded that alignment targets should be proportional to PI. 19 Using mechanical complications as a composite outcome, the authors categorized 4 radiographic parameters using optimal cutoffs based on the outcome of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to define a thoracic alignment relative to lumbar alignment and using postural measures (eg, pelvic tilt or sagittal vertical axis) has likely contributed to the poor external validity of current alignment guidelines. [14][15][16][17][18] Our results redefine what should be considered a normal sagittal alignment and fill a critical knowledge gap. In our first aim and consistent with prior studies on sagittal balance, we found C2 tilt (also known as the Odontoid-Hip-Axis) had minimal variation and is an ideal measure of global sagittal balance.…”
Section: Discussionmentioning
confidence: 59%
“…However, PI explains only a fraction of the variation observed in normal lumbar lordosis. Furthermore, currently accepted alignment targets utilize postural measures (eg, pelvic tilt, sacral slope, or sagittal vertical axis) that are not directly modifiable in surgery, and none of the targets define a reliable method for alignment the thoracic spine, likely contributing to the poor external validity of current alignment guidelines 14–18…”
mentioning
confidence: 99%
“…Meta-analyses of 2 studies reported no relationship between uppermost instrumented vertebrae (UIV) above T6, UIV below T6, lower instrumented vertebrae (LIV) to the sacrum and relationship to the development of implant-related complications (data not shown). 19,20 Individually reported independent risk factors for implant-related complications included increased age at surgery, greater postoperative global tilt, greater preoperative thoracolumbar kyphosis, and pedicle subtraction osteotomy at S1. 19,21 Risk Factors for PJK…”
Section: Risk Factors For Medical Complicationsmentioning
confidence: 99%
“…19,20 Individually reported independent risk factors for implant-related complications included increased age at surgery, greater postoperative global tilt, greater preoperative thoracolumbar kyphosis, and pedicle subtraction osteotomy at S1. 19,21 Risk Factors for PJK…”
Section: Risk Factors For Medical Complicationsmentioning
confidence: 99%